Are green bonds priced differently from conventional bonds?. Issue 6 (October 2018) - Hachenberg, Britta; Schiereck, Dirk
Abstract The young growing market for green bonds offers investors the opportunity to take an explicit focus on climate protecting investment projects. However, it is an open question whether this new asset class is also offering attractive risk–return profiles compared to conventional (non-green) bonds. To address this question, we match daily i-spreads of green-labeled and similar non-green-labeled bonds and look at their pricing differentials. We find that rating classes AA–BBB of green bonds as well as the full sample trade marginally tighter for the respective period compared to non-green bonds of the same issuers. Furthermore, financial and corporate green bonds trade tighter than their comparable non-green bonds, and government-related bonds on the other hand trade marginally wider. Issue size, maturity and currency do not have a significant influence on differences in pricing but industry and ESG rating.